THE CONTENTS OF NEUTRAL AND POLAR LIPIDS IN CLOSTRIDIA CELLS UNDER CULTIVATION IN THE PRESENCE OF BUTANOL - S. I. Voychuk (Biotechnologia Acta, 2017)
The aim of the study was to evaluate changes in the portion of polar and neutral lipids in the cells of Clostridium during their cultivation in the presence of butanol. Four natural isolates of Clostridium genus were studied with flow cytometry approaches. Under the optimal culture conditions, the polar lipids prevailed over neutral ones in bacterial cells; the content of neutral lipids doubled in spores of these microorganisms, while the content of polar ones was reduced. Strains No 1 and No 2 were able to grow at 1% butanol in the medium, and the strain No 4 was at 1.5%. When cultivated in the presence of different concentrations of butanol, the bacterial strains did not differ in such cytomorphological features as granularity and cell size. The quantitative content of polar and neutral lipids in the presence of butanol varied depending on the content of butanol in the medium, however this effect had a strain-specific character and did not show a correlation with the resistance of these bacteria to butanol. So, the content of polar and neutral lipids varied depending on butanol content in the medium. However this effect was strain-specific independently of resistance of these bacteria to butanol. The use of bacterial biomass as a source of lipids for the production of biofuels requires further optimization of the process to increase the content of the neutral lipid fraction in bacterial cells.